Cu-Containing Faujasite-Type Zeolite as an Additive in Eco-Friendly Energetic Materials - Łukasz Kuterasiński; Marta Sadowska; Paulina Żeliszewska; Bogna Daria Napruszewska; Małgorzata Ruggiero-Mikołajczyk; Mateusz Pytlik; Andrzej Biessikirski (Molecules, 2024)
Regarding the current state of the art on the utilization of zeolites in industry, the application of zeolites as an additive to eco-friendly energetic materials indicates the innovative character of the present research. One of the most commonly used energetic materials in the mining industry (engineering works) is ANFO (ammonium nitrate fuel oil), due to its easy and cheap production procedure as well as its good energetic properties and vast possibilities for modification. In the present research, we investigated Cu-zeolite with a faujasite structure (Cu-FAU) as a modifier of ANFO-based energetic materials. Analysis of the results obtained from thermodynamic calculations of energetic performance led to the conclusion that the application of Cu-faujasite as an additive to ANFO resulted in a relevant reduction in the total emission of post-decomposition fumes, with simultaneous enhancement of the energetic properties of the energetic material, which corresponded with the changes in the status of the surface and the reduced thermal effect accompanying the ammonium nitrate’s decomposition. From analysis of both the energetic performance and fumes, it may be concluded that our eco-friendly and enhanced energetic material can be used as a low-emission source of energy for the quarrying of raw materials.